Common musculoskeletal problems a handbook - Daniels, James M.; Hoffman, M. Rebecca (Mary Rebecca).; SpringerLink (Online service). (New York Springer, 2010)
Common Musculoskeletal Problems in Primary Care: A Handbook is an excellent point of care resource for health care providers to better diagnose and treat patients presenting with common musculoskeletal complaints. Each chapter in this book focuses on a specific joint or region and discusses anatomy, red flags, approach to the patient, common clinical presentations and management, and includes a flow diagram to help direct management and follow-up of a patient?s problem. A user-friendly approach makes this handbook an ideal reference for medical students, primary care residents, and practicing primary care providers alike.
Introduction -- The Cervical Spine -- The Shoulder -- The Elbow -- The Hand and Wrist -- The Lumbosacral Spine -- The Hip -- The Knee -- The Ankle -- Common Pediatric Musculoskeletal Problems -- The Acutely Painful, Swollen Joint -- Muscuoloskeletal Radiology -- Splinting and Soft Tissue Issues -- Pre-participation Evaluation -- Appendix.
Electronic reproduction.
Keywords: Musculoskeletal system -- Diseases -- Diagnosis; Musculoskeletal system -- Wounds and injuries; Primary care (Medicine); Electronic books